Biosolarization, and efficient alternative for disinfection and reuse of substrates in a garden-orchard - Puerta, Analia Veronica; Rubio, Esteban Julian; Santos, M.; Pitarch, R.; Karlanian, Monica; Mantilla Alarcon, Alfredo Gunther (2025)
Presentación en diapositivas